Character Building in Early Childhood: Insights from the Living Values Education Program (LVEP) - Muadhinah, Nana; Munawwarah, Munawwarah (IKIP Siliwangi, 2024)
Character education is crucial, especially in Indonesia, where societal values, norms, and morals are increasingly deviating. Many individuals involved in these deviations are from the younger generation, particularly school-aged children. This research adopts a qualitative approach, with the principal and three teachers from each class serving as the primary data sources. Data collection methods include observation and interviews using instruments such as observation guidelines and interview guidelines. Data analysis which consists of data reduction, data presentation, and conclusion drawing. The findings of the study reveal significant changes in children's character development post-evaluation. Improvements were observed in several areas: emotional regulation (children are better able to manage their emotions), social skills (increased ability to share and cooperate), independence (greater confidence in decision-making), discipline (more rule-abiding and organized), moral development (enhanced understanding of right and wrong), and motor skills (better physical coordination). These changes varied depending on the methods employed and the individual characteristics of each child.